Manual, automatic and shared methods for controlling an intelligent wheelchair: Adaptation to cerebral palsy users - Faria, Brigida Monica (2019)
The development of an intelligent wheelchair (IW) platform that may be easily adapted to any commercial wheelchair and aid any person with special mobility needs is the main objective of this project. To be able to achieve this main objective, three distinct control methods were implemented in the IW: manual, shared and automatic. Several manual, shared and automatic control algorithms were developed for this task. This paper presents three of the most significant of those algorithms with emphasis on the shared control method. Experiments were performed, using a realistic simulator, with real users suffering from cerebral palsy in order to validate the approach. These experiments enabled to conclude which were the best shared control methods to implement on the IW. The experiments also revealed the importance of using shared (aided) controls for users with severe disabilities. The patients still felt having complete control over the wheelchair movement when using a shared control at a 50% level and thus this control type was very well accepted and should be used in intelligent wheelchairs since it is able to correct the direction in case of involuntary movements of the user but still gives him a sense of complete control over the IW movement.